Opisno ocenjevanje pri likovni vzgoji v prvem triletju - Duh, Matjaž; Kolar, Rebeka; Rezar, Lea (Revija za elementarno izobraževanje, 2009)
Descriptive assessment in art classes in the first three years of primary school. The article describes the problems of descriptive assessment, which in Slovenia, is used during the first three years of primary school. We focussed special attention on descriptive assessment in Art Education. According to the opinion of many experts, descriptive assessment is of more quality than numerical assessment. Moreover, it is also much more illustrative, for it describes all the pupil's (un)attained goals or standards of knowledge. However, as the mentioned method presents an additional burden for the teachers, simple copying of the goals or standards of knowledge which later form the descriptive mark for every individual pupil is becoming increasingly frequent. This has been especially well presented in Art Education. In our research we checked the current state in the field of descriptive assessment in Art Education. With the quantitative and qualitative research, performed on the basis of a questionnaire and examples of summative descriptive marks in Art Education, we examined teachers' opinions on descriptive assessment and how this method is truly being practiced. We discovered that most of the teachers are satisfied with the method. Furthermore, the questionnaire also revealed that most of them also take all the advice given. On the contrary, the analysis of the summative descriptive marks in Art Education revealed just the opposite; individualisation had been rarely considered, and the Art Education programme was noted for its extremely obvious, nearly identical, descriptive marks.